2021
DOI: 10.3389/fonc.2020.606300
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Lung Cancer Driver Genes Associated With Brain Metastasis

Abstract: Brain metastasis, one of the common complications of lung cancer, is an important cause of death in patients with advanced cancer, despite progress in treatment strategies. Lung cancers with positive driver genes have higher incidence and risk of brain metastases, suggesting that driver events associated with these genes might be biomarkers to detect and prevent disease progression. Common lung cancer driver genes mainly encode receptor tyrosine kinases (RTKs), which are important internal signal molecules tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 165 publications
2
11
0
Order By: Relevance
“…Brain metastasis is likely to have a parallel evolutionary model. Tumor driver gene-associated signaling pathways are crucial for promoting tumor cell survival, invasion, and colonization in the CNS [8]. These findings elucidate the biology of CNS metastasis in lung cancer and may lead to the development of a novel approach to preventing CNS metastasis.…”
Section: Introductionmentioning
confidence: 83%
“…Brain metastasis is likely to have a parallel evolutionary model. Tumor driver gene-associated signaling pathways are crucial for promoting tumor cell survival, invasion, and colonization in the CNS [8]. These findings elucidate the biology of CNS metastasis in lung cancer and may lead to the development of a novel approach to preventing CNS metastasis.…”
Section: Introductionmentioning
confidence: 83%
“…According to histopathology, lung cancer can be divided into non-small cell lung cancer (NSCLC), which accounts for 85% of lung cancer cases, and small cell lung cancer (SCLC) that accounts for 15%. Among all cancer types, lung cancer has the highest incidence of BM among all types of cancers [ 128 ]. Upon diagnosis, around 10–25% of lung cancer patients present with BM and 40–50% of such patients will develop BM during the course of the disease [ 129 ].…”
Section: Extravasation Of Tumor Cells Through the Blood–brain Barrier...mentioning
confidence: 99%
“…The provision of education in various formats was found to increase carers' knowledge of delirium across all studies. Carers' knowledge of risk factors and prevention strategies for delirium was reported to improve in four studies, 27,29,30,33,34 and was sustained following discharge in one study. 27 Studies that implemented strategies to also improve nurses' knowledge of delirium reported the carers feeling better-prepared for caregiving, feeling less anxious about providing care following discharge and having a more positive relationship with the person they cared for.…”
Section: Increasing Knowledgementioning
confidence: 99%